2018
DOI: 10.1002/lary.27604
|View full text |Cite
|
Sign up to set email alerts
|

Association of epistaxis with atherosclerotic cardiovascular disease

Abstract: Objectives/Hypothesis To investigate the association between epistaxis and atherosclerotic cardiovascular disease. Study Design Case‐control cohort study. Methods This study included patients from the tertiary‐care ear, nose, and throat department at the University Hospital of Zurich between December 1, 2016 and June 1, 2017. We assessed the cardiovascular risk profiles in a group of 41 patients presenting with epistaxis, and a group of 41 matched controls, focusing on a surrogate parameter for atherosclerosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Regarding the clinical characteristics of the patients; we showed that the mean age of the study patients was 27.25± 13.92 years, ranged from 12 to 70 years. These results were in similar to Rahmanzadeh-Shahi et al, (2018); who showed that the mean age of patients with epistaxis was 40.22 ± 2.07), but it was lower than Lou and Lou, (2019) and Kunz et al, (2018); who showed that the mean age was 72.4 ± 5.1 years and 74.2 ± 13.6 years respectively. Moreover, Brown et Our work showed that right-sided epistaxis occurred in 45%, then bilateral epistaxis (30%), and lastly the left-sided epistaxis (25%).…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the clinical characteristics of the patients; we showed that the mean age of the study patients was 27.25± 13.92 years, ranged from 12 to 70 years. These results were in similar to Rahmanzadeh-Shahi et al, (2018); who showed that the mean age of patients with epistaxis was 40.22 ± 2.07), but it was lower than Lou and Lou, (2019) and Kunz et al, (2018); who showed that the mean age was 72.4 ± 5.1 years and 74.2 ± 13.6 years respectively. Moreover, Brown et Our work showed that right-sided epistaxis occurred in 45%, then bilateral epistaxis (30%), and lastly the left-sided epistaxis (25%).…”
Section: Discussionsupporting
confidence: 88%
“…Instead, a history of IHD and normal haemoglobin on admission were found to be independent predictors of re‐bleeding following pack removal. Strong association between severe epistaxis and IHD has been previously described 11 . The findings of this study suggest a lower chance of pack success in those with a history of IHD but further research is needed to determine if a causative relationship exists.…”
Section: Discussionsupporting
confidence: 58%
“…However, the reduction of elastic fibres with subsequent collagen accumulation leads to arterial stiffening and intima-media thickening, which are independent predictors of incident hypertension in prospective community-based studies 22 . Kunz et al 23 mentioned that it is crucial to identify individuals with an increased atherosclerotic burden before such life-threatening events take place. The occurrence of severe epistaxis in his study was shown to be closely associated with the prevalence of atherosclerotic cardiovascular disease by analysing the carotid intima-media thickness by means of an ultrasonographic study 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Kunz et al 23 mentioned that it is crucial to identify individuals with an increased atherosclerotic burden before such life-threatening events take place. The occurrence of severe epistaxis in his study was shown to be closely associated with the prevalence of atherosclerotic cardiovascular disease by analysing the carotid intima-media thickness by means of an ultrasonographic study 23 .…”
Section: Discussionmentioning
confidence: 99%